FEATURES OF HISTORICAL AND CULTURAL HERITAGE FORMATION IN KHARKIV REGION - Шпурік, Катерина (Human Geography Journal, 2014)
The article analyzes the regional characteristics and most significart socio-economic factors of historical and cultural heritage formation in Kharkiv region. The appearance of historical and cultural sites during different historical periods is characterized. periods of economic development on the territory of modern Kharkiv region, which had the greatest influence on the formation of distinctive cultural landscape and left the greatest number of unique objects, are determined applying the principle of chronological of historians.